Alexander's Law During High-Speed, Yaw-Axis Rotation: Adaptation or Saturation? - Lädrach, Claudia; Zee, David S.; Wyss, Thomas; Wimmer, Wilhelm; Korda, Athanasia; Salmina, Cinzia; Caversaccio, Marco D.; Mantokoudis, Georgios (Frontiers in Neurology, 2020)
Objective: Alexander's law (AL) states the intensity of nystagmus increases when gaze is toward the direction of the quick phase. What might be its cause? A gaze-holding neural integrator (NI) that becomes imperfect as the result of an adaptive process, or saturation in the discharge of neurons in the vestibular nuclei? Methods: We induced nystagmus in normal subjects using a rapid chair acceleration around the yaw (vertical) axis to a constant velocity of 200°/second [s] and then, 90 s later, a sudden stop to induce post-rotatory nystagmus (PRN). Subjects alternated gaze every 2 s between flashing LEDs (right/left or up/down). We calculated the change in slow-phase velocity (ΔSPV) between right and left gaze when the lateral semicircular canals (SCC) were primarily stimulated (head upright) or, with the head tilted to the side, stimulating the vertical and lateral SCC together. Results: During PRN AL occurred for horizontal eye movements with the head upright and for both horizontal and vertical components of eye movements with the head tilted. AL was apparent within just a few seconds of the chair stopping when peak SPV of PRN was reached. When slow-phase velocity of PRN faded into the range of 6–18°/s AL could no longer be demonstrated. Conclusions: Our results support the idea that AL is produced by asymmetrical responses within the vestibular nuclei impairing the NI, and not by an adaptive response that develops over time. AL was related to the predicted plane of eye rotations in the orbit based on the pattern of SCC activation.